Embracing digital disruption in translator training: technology immersion in simulated translation bureaus - Joost Buysschaert; María Fernández-Parra; Koen Kerremans; Maarit Koponen; Gys-Walt van Egdom (My University, 2022)
The aim of the present article is to show how the holistic approach of a “simulated translation bureau” (STB), bringing together many technological skills that would otherwise be taught separately in isolated course units, succeeds in familiarising translation students with the new ways of working and with new technologies.